# Which quadratic equation is equivalent to (x + 2)^{2} + 5(x + 2) – 6 = 0?

An equation of the form ax^{2 }+ bx + c = 0, where a ≠ 0 is called a quadratic equation.

## Answer: x^{2} + 9x + 8 = 0 is the equivalent quadratic equation to (x + 2)^{2} + 5(x + 2) – 6 = 0.

Let us simplify the given quadratic equation.

**Explanation:**

(x + 2)^{2} + 5(x + 2) – 6 = 0

x^{2} + 2(x)(2) + 4 + [5x + 10] - 6 = 0

x^{2} + 4x + 4 + 5x + 10 - 6 = 0

x^{2} + (4 + 5)x + (10 - 6 + 4) = 0

x^{2} + 9x + 8 = 0

### Thus, x^{2} + 9x + 8 = 0 is the equivalent quadratic equation to (x + 2)^{2} + 5(x + 2) – 6 = 0.

Math worksheets and

visual curriculum

visual curriculum